Adjuvant sorafenib for hepatocellular carcinoma after radiofrequency ablation versus radiofrequency ablation: analysis of its efficacy and safety - Junxiao, Wang; Rui, Liu; Zhenyu, Wen; Zejie, Sang; Xiang, Yang; Mingchao, Ding; Hui, Xie (Frontiers in Oncology, 2024)
ObjectivesFor the treatment of early hepatocellular carcinoma, we compared the efficacy and safety of radiofrequency ablation (RFA) alone and radiofrequency ablation combined with sorafenib (RFA+Sor).MethodsA total of 164 patients with early HCC were included in the study. There were 87 patients who underwent RFA alone, and 77 patients who underwent RFA+Sor treatment. Overall survival (OS) was the primary endpoint of the study, and recurrence-free survival (RFS) and safety were the secondary endpoints.ResultsAccording to the RFA group, the RFS rates were 74.7%, 29.9%, and 11.5% at 1, 2, and 3 years, whereas in the RFA+Sor group, the RFS rates were 72.7%, 19.5%, and 11.7% at 1, 2, and 3 years (P>0.05). RFA and RFA+Sor groups had median OS of 35.0 and 41.0 months, respectively (P>0.05). For the RFA and RFA+Sor groups, the median RFS was 17.0 and 16.0 months, respectively (P>0.05). Based on the univariate regression analysis, there was no statistically significant difference between the subgroups (P>0.05). Skin rashes only occurred in the RFA+Sor group, and other adverse effects were not significantly different between the two groups (P>0.05).ConclusionsTreatment with RFA+Sor treatment did not result in a longer OS than treatment with only RFA, however, the adverse effects of adjuvant Sorafenib were acceptable.